Adsorption–biodegradation coupled remediation process for the efficient removal of a textile dye through chemically functionalized sugarcane bagasse. (22nd June 2021) - Gita, Samchetshabam; Shukla, Satya Prakash; Deshmukhe, Geetanjali; Singh, Arvind Rajdeo; Choudhury, Tanmoy Gon; Singh, Ashutosh Kumar
Abstract: Textile dye effluents have many deleterious effects; therefore, it is essential to remove before releasing into waterbodies. This study developed a two‐step process for decolorization of textile dye using sugarcane bagasse (SCB). The first step of the process involved functionalization of SCB with alginic acid and applying as packing material in column and assessing its performance for adsorptive removal of Drimarene red. The designed column showed 90% removal of the dye in dye‐aqueous solution whereas 80% removal in dye‐house wastewater. Adsorption capacity was increased at first 10 min and then gradually decreased with time. Breakthrough point was not achieved during the 60 min of experiment. Three non‐equilibrium models were applied to understand the column bed properties. In the second step, the adsorbed dye molecules in SCB were degraded using an edible fungus Pleurotus sp. to obtain a dye‐free nitrogen‐rich bagasse. The fungus‐treated SCB showed no residual toxicity and a considerable improvement in nitrogen content (from 0.14% to 0.62%) was noticed after the study of elemental profile. New design of the column bed, the processes of the chemical functionalization of the SCB, and bioremediation of dye treated bagasse through Pleurotus sp. offer a novel solution for efficient and safe disposal of textile dyes. Practitioner Points: Two‐step process for remediation of a textile dye using an agrowaste and Pleurotus sp. Chemical functionalization of an agrowaste for enhanced dye removal. New process of adsorption–fungal degradation for safe disposal of the dyes. Novel technology for a sustainable use of the agrowaste for environmental safety. Abstract : Aiming for low‐cost remediation of a textile dyes, a two‐step remediation protocol involving adsorptive removal using chemically functionalized sugarcane bagasse followed by biodegradation through a non‐toxic fungus ( Pleurotus sp .) was developed and validated. The used bagasse ameliorated through fungal degradation in the second step of the protocol produced nitrogen‐rich bagasse.